Pensar e viver para além das categorias do real e do irreal: Merleau-Ponty e o imaginário operante - Annabelle Dufourcq (DoisPontos, 2012)
The dimension of violence and the radically destabilizing implications of Merleau-Ponty’s thought are sometimes, too often, overlooked. The merleau-pontian flesh is not first and foremost peaceful, it is an explosive and open being, within which self-coincidence, rest and truth in a classical sense are impossible. This article intends to demonstrate that MP makes the classical distinction between the real and the unreal collapse, entailing a deep reorganization of the fields of knowledge and ethics and, somehow, a fusion between them. If the very being is unfinished and open to interpretations, then there is no truth to be known, we only have “images” of the world and, correlatively, images are more revealing of the on-going meaning in which the world consists than any so-called absolute knowledge. Moreover, to accept the creative dimension of interpretation as requested by the world itself permits to realize that one cannot understand the world without acting and that to act is to set up a balance between, on the one hand, the patient attention paid to the nascent meaning in situations and, on the other hand, a bold shaping of the given elements of meaning that are always “in-themselves” scattered and ambiguous.